Competition and Collaboration in the Contracting of Family Relationship Centres - Butcher, John; Freyens, B. (Blackwell Publishing, 2011)
In 2005-06 the Australian government announced the establishment of 65 Family Relationship Centres (FRCs) - a 'gateway' service assisting separating couples to reach agreement about child custodial arrangements without recourse to courts. The use of a multi-round competitive contracting regime for the purpose of selecting service providers gave rise to a number of tensions amongst not-for-profit organisations (NFPOs) which, to a degree, compromised the full realisation of stated public policy aims. Reporting on fieldwork conducted with a sample of FRC operators, industry representatives and key government officials this article evaluates the extent to which the case of FRCs conforms to critiques commonly aired in the social policy literature that attribute various forms of policy failure and/or social capital depletion to the competitive contracting of human services within quasi-markets. Although the competitive selection process imposed significant costs on the NFPOs involved, the program also exhibited substantial collaborative and collegial behaviours between government and NFPOs, thus diverging from the critique usually portrayed in the literature.